PANDANGAN FILSAFAT HUMANISME TERHADAP PENDIDIKAN - Devi, Devi Fitria Sabila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to discuss the perspective of humanistic philosophy, which places humans as unique individuals with the potential to grow and develop. The emphasis of humanism lies in individual potential, self-awareness, freedom and autonomy, potential achievement, subjective experience, and social relationships, such as the provision of emotional values. The purpose of writing this article is to determine how the humanist philosophy flows in education. This study uses a library research method (literature review) with a descriptive approach. The data collection method relies on relevant literature sources. In this approach, the researcher collects, reads, and analyzes various scientific papers, books, journals, and other documents related to the research topic. The results show that humanist theory encourages a more holistic approach to education and emphasizes individual growth and the development of interpersonal skills. The humanist educational approach has a positive impact on students' spiritual development, not only understanding but also humanism pays attention to the development of moral, ethical, and leadership aspects. Along with the development of the times, the integration of humanist values ​​​​needs to be carried out carefully, so that the values ​​​​of Islamic religious education are not eroded and remain consistent. Keywords: philosophy of humanism, education